2008
DOI: 10.1002/mame.200800134
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanical Properties of Poly(lactic acid) Filled with (Starch nanocrystal)‐graft‐poly(ε‐caprolactone)

Abstract: Poly(ε‐caprolactone) (PCL) was grafted to the surface of starch nanocrystals (StN) via microwave‐assisted ROP. The resultant nanoparticles were then incorporated into a poly(lactic acid) matrix to produce fully‐biodegradable nanocomposites with good mechanical properties. A loading level of 5 wt.‐% StN‐g‐PCL resulted in simultaneous enhancements of strength and elongation. The StN‐g‐PCL self‐aggregated as rubbery microparticles to enhance the elongation by ca. 10‐fold over that of neat PLA. Meanwhile, the graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(61 citation statements)
references
References 37 publications
(40 reference statements)
3
57
0
1
Order By: Relevance
“…However, the L/D ratio for SNs was far smaller than the former value [10], and the SNs looked like round particles and a decrease of elongation with the increase of SNA in the matrix was observed. Furthermore, higher SNA loading level resulted in a decrease of the elongation due to the self-aggregation of SNA, and similar results were reported by other authors [16,21,22,30]. The above results indicated that there might be an underlying structure whose formation controls the tensile performance evolution with SNA content.…”
Section: Tensile Testssupporting
confidence: 89%
“…However, the L/D ratio for SNs was far smaller than the former value [10], and the SNs looked like round particles and a decrease of elongation with the increase of SNA in the matrix was observed. Furthermore, higher SNA loading level resulted in a decrease of the elongation due to the self-aggregation of SNA, and similar results were reported by other authors [16,21,22,30]. The above results indicated that there might be an underlying structure whose formation controls the tensile performance evolution with SNA content.…”
Section: Tensile Testssupporting
confidence: 89%
“…Chitin whiskers were isolated and polycaprolactone grafted (CHW-g-PCL) in view of preparing thermoformable bionanocomposites [31][32][33][34] . The grafting was achieved by initiating the ring-opening polymerization ("grafting from" strategy) of caprolactone monomer onto the CHW surface under microwave radiation.…”
Section: Nanocompositesmentioning
confidence: 99%
“…The purified product was vacuum-dried, and coded as StN-g-PCL. In our previous report, 29 the grafted PCL content in StN-g-PCL was determined, by element analysis, to be 84.16 wt %. TEM images showed most of the StN-g-PCL nanoparticles were platelet-like in structure and less than 100 nm (Fig.…”
Section: Extraction and Grafting Of Starch Nanocrystalsmentioning
confidence: 99%
“…27,28 In this work, the surface of starch nanocrystals (StN) was functionalized by grafting polycaprolactone (PCL) chains based on the ''graft from'' strategy from our previous work. 29 The soft-segment, with the same origin as grafted PCL chains, was therefore selected as the component of waterborne polyurethane matrix. Compared with the previous report on the Poly(1,4-butylene glycol adipate)-based waterborne polyurethane modified by neat StN, 28 the same structure for soft-segment and grafted chains on the surface of StN could improve the association between waterborne polyurethane as matrix and the StN-g-PCL nano-filler.…”
Section: Introductionmentioning
confidence: 99%